Drinkers’ Perceptions on Conducting Studies on Alcohol Consumption: Preliminary Study for International Alcohol Control Study, Turkey - Sandıklı, Büşra; Torun, Perihan; Balcı Yapalak, Ayşe Nur (Addicta: The Turkish Journal on Addictions, 2020)
Lack of policy-oriented research in Turkey could be attributed to the perceptions of researchers on existence of an alcohol use problem in the population, methodological difficulties of conducting alcohol research, and the perceived sensitivity of the topic in the population. This descriptive quantitative study was carried out before the conduct of the International Alcohol Control Study (IAC) in Turkey, with an aim to assess the knowledge, attitude, and behaviors on alcohol research of 142 adults aged 18 years and above, who have the experience of consuming alcohol, to determine their preference for interviewer characteristics, interview place, and research institution. More than half of the participants (54.9%) stated that alcohol consumption studies were necessary, and a majority (74.7%) was willing to participate in such a study. The participants believed that the alcohol consumers from their own social environments would express their drinking status openly (72.5%) and report their consumption accurately (70.4%). Use of political or religious symbols by the interviewers did not seem to influence responses for more than half of the study subjects, although a non-negligible group have not agreed. The participants favored World Health Organization as the research institution (53.2%) and medical students (62.9%) as the interviewers.
Keywords: Alcohol; alcohol consumption; alcohol research; international alcohol control study (IAC); interviewer